Relationship between high level young handball goalkeepers` playing characteristics and body composition - Visnapuu, M.; Jürimäe, T.; Jürimäe, J.; Allikivi P. (EHF Scientific Conference 18.-19.11.2011, Wien, Österreich, 2011)
Aims of the study: Investigate the relationship between playing characteristics and anthropometrical parameters in young high performance goalkeepers. Subjects: 40 young male goalkeepers were studied at the 2006 European U18 Championships. Conclusion: According to the present study anthropometrical parameters are poor predictors of playing characteristics of young high-level handball goalkeepers.